A Novel Biosensor Based on Acetylecholinesterase/Chitosan-Graphene Oxide Modified Electrode for Detection of Carbaryl Pesticides - Li, Pengcheng; Song, Yonghai; Chen, Souhui; Zhang, Mei; Wang, Li (Asian Journal of Chemistry, 2013)
A sensitive, fast and cheap sensor for quantitative determination of carbaryl pesticide using amperometric acetylcholinesterase biosensor based on graphene oxide-chitosan hybrid film was reported. This biosensor was fabricated by firstly depositing chitosan-graphene oxide hybrid film on glassy carbon electrode and subsequently assembling acetylcholinesterase on chitosan-graphene oxide hybrid film. The chitosan-graphene oxide hybrid film exhibited a good biocompatibility with acetylcholinesterase and effective immobilization of acetylcholinesterase. The resulted biosensor showed a good electrocatalytic activity toward oxidation of thiocholine, which was a product from the hydrolysis of acetylthiocholine catalyzed by acetylcholinesterase. The inhibition of carbaryl on the activity of acetylcholinesterase was proportional to carbaryl concentration in the range from 0.005 to 0.4 μM and from 1.0 to 5.0 μM, respectively. The detection limit was calculated to be about 4.0 nM. The biosensor provided a new promising tool for pesticide analysis.